Big data analytics for adaption to climate change. Issue 1 (1st October 2022) - Wang, Haijing; Wang, Yaping
Abstract: Big data analytics (BDA) has the 5-v benefit of volume, variety, veracity, velocity, and value and has the potential to help adaptation to climate change. This paper reports the preconditions for designing the BDA system specifically for adapting to climate change, the designing of this BDA system, and the actual performance. In terms of layers, the components of the BDA system have five integrated layers: the persistent layer, the distributed data storage indexing layer, the web-based data analytics layer, the web-based layer responding to web-based requesting portals, and the web portal layers for specialist administrators to make responses. The BDA system includes the primary database, the sectoral database, and the integration process. The BDA generally met the preconditions and the goals of improving the adaptation capacity to climate change. The trial use of this BDA covered seven provinces in terms of geographic areas and covered preventing flood, tracing diseases caused by climate change, zoning and planning urban areas, and other fields in terms of content. The actual performance indicates that this BDA system functions well as to the speed of processing, the soundness of analysis, and the accuracy of data. However, there is still a need to improve its capacity to spot and detect erroneous but non-conflicting data.